Comparison of the change in posterior corneal elevation and corneal biomechanical parameters after small incision lenticule extraction and femtosecond laser-assisted LASIK for high myopia correction. Issue 3 (June 2016) - Wang, Bingjie; Zhang, Zhenyong; Naidu, Rajeev K; Chu, Renyuan; Dai, Jinhui; Qu, Xiaomei; Yu, Zhiqiang; Zhou, Hao
Highlights: Posterior corneal elevation (PCE) changes and corneal biomechanical parameters were evaluated for SMILE and FS-LASIK. PCE change in FS-LASIK was greater than SMILE at 12 months post-operation. CH and CRF were reduced for both procedures at 6 and 12 months, FS-LASIK demonstrated a greater reduction in CRF than SMILE. PCE was moderately correlated with CH and CRF change, indicating an increase in PCE with greater reduction in CH and CRF. Abstract: Purpose: To compare posterior corneal elevation (PCE) changes and corneal biomechanical changes post fematosecond laser-assisted laser in situ keratomileusis (FS-LASIK) and small incision lenticule extraction (SMILE) procedures using the Pentacam system and the Ocular Response Analyzer (ORA). Design: Retrospective observational case series study. Method: 106 patients with bilateral myopia who underwent either FS-LASIK (56 patients) or SMILE (50 patients) were reviewed, only the right eye was used in the analysis. Inclusion criteria include a spherical equivalent of −6.00DS and completion of 12 months follow up. The main outcome evaluated was change in PCE at 3 months, 6 months and 12 months post-operation using the Pentacam system. Corneal biomechanical parameters were evaluated at 6 and 12 months with the ORA. Results: PCE change at 3 and 6 months were not significantly different between the two procedures ( p = 0.064, p = 0.109 respectively). At 12 months, PCE change was greater in FS-LASIK than SMILE ( p = 0.048). One-way ANOVA showed that for either procedure, the change in PCE did not differ at 3, 6 or 12 months post operation. CH and CRF values were reduced after both procedures, with FS-LASIK demonstrating a greater reduction in CRF than SMILE at 6 and 12 months ( p = 0.037 and p = 0.001). Both CH and CRF reduction correlated with PCE increase at 6 and 12 months. Conclusion: FS-LASIK demonstrated a greater increase in PCE than SMILE only at 12 months, as well as a greater reduction of CRF than SMILE. There were no significant differences in PCE change over time within either group.